Lesson 7: To use the 'Make ten' strategy to subtract a 1-digit number from a teen number (Part 1) - Oak National Academy (Teacher Hub | Oak National Academy)
Lesson: To use the 'Make ten' strategy to subtract a 1-digit number from a teen number (Part 1)
Keywords: _C:United Kingdom GBR